The altmetrics for measuring readers’ intentions towards scholarly contents in the field of information security - HALIMA SALEH ALI AL BALUSHI; NAWAL ALI ABDULLAH AL BULUSHI; RABAB JUMA MOHAMMED AL-RIYAMI (Journal of Advanced Research in Social Sciences and Humanities, 2018)
Aim: This research aimed to examine the relationship between citations (Bibliometrics) and readers’ intentions (Altmetrics) for each type of scholarly document by applying altmetrics tools to measure their attitudes toward highly cited content in the field of information security.Method: Scopus was used to identify the most prolific types of documents published in the field of information security in the years 2014 and 2015, as this was thought to be an appropriate time frame for the scholarly production to be freely accessible in full text and, consequently, for the right to use and cite to be taken, as well as for the production to be used and interacted with across various social media channels. Among scholarly writing, conference papers, articles, and book chapters fared best. We picked the 20 most-cited articles from each document type to gauge reader intent and analysed them.Findings: This research found that articles received the most citations among all document types studied, followed by conference papers and book chapters. Articles that received the most citations also attracted the most reader intent. Given the interconnected nature of citations and goals, this finding makes sense. The correlation was impacted by the variety of documents used. Based on the data, it is clear that the articles are the ones to which the correlation between citations and attention is strong. The most interesting citations were for the articles about intentions.Implications/Novel contribution: This research significantly contributes to the body of literature because it provides detailed information about citations and article publications.